Association between days for concussion recovery and initial specialty clinic evaluation within 48 hours - Abel S. Mathew; Todd Caze; August M. Price; Desi Vasquez; John P. Abt; Scott O. Burkhart (BMC, 2024)
Abstract Background Researchers have highlighted the importance of early access to concussion care within one week of injury in reducing recovery times. However, a persisting question for concussion researchers is "just how early is important?" The purpose of this study was to examine differences in recovery time as predicted by the number of days elapsed since injury (DSI) to initial evaluation among patients who had access to a specialty concussion clinic within seven days. We hypothesized that DSI group membership, even within seven days, would significantly predict risk of protracted recovery (i.e., beyond 21 days). Methods In this archival study, retrospective data were gathered from electronic medical records between September 2020 to March 2022. Records of participants between ages 12-18, those diagnosed with a sports-related concussion based on initial clinic visit diagnosis by a medical provider and those who established care within seven days of injury at a large pediatric specialty concussion clinic were examined. Participants were divided into three DSI groups (patients seen in < 48 h: "acute", patients seen between 49 h < and < 96 h: "sub-acute", and patients seen between 97 < and < 168 h: "post-acute"). A general linear model was constructed to examine relationships between relevant concussion factors (e.g., Post Concussion Scale Score, neurodevelopmental history, psychiatric history, concussion history, migraine history, overall VOMS change score, cognitive testing, sex, age, race, and ethnicity) that were either significant in the preliminary analysis or in clinical judgement and recovery time. Adjusted odds ratios (OR) were derived from a binary logistic regression model, in which recovery time was normal (≤ 21 recovery days) or protracted (> 21 recovery days). Results A total of 856 participants were eligible. Adolescents in the acute group (M = 15.12, SD = 8.04) had shorter recovery times in days compared to those in the sub-acute (M = 17.98, SD = 10.18) and post-acute (M = 21.12, SD = 10.12; F = 26.00, p < .001) groups. Further, participants in the acute (OR = 4.16) and sub-acute (OR = 1.37) groups who accessed specialty concussion clinics within 48 h were 4 times more likely to have a normal recovery and recovered approximately 6 days faster than the post-acute care group. Conclusions Earlier concussion care access predicted recovery times and was associated with lower risk for protracted recovery.